Efficient adsorptive removal of hazardous congo red dye using Ce-BTC@microcrystalline cellulose composite - Mostafa A. Sayed; Reda M. Abdelhameed; Ibrahim H. A. Badr; Ali M. Abdel-Aziz (Scientific Reports)
Abstract In this research, we developed a novel composite material, Ce-BTC@MCC, by combining a metal-organic framework (Ce-BTC) with microcrystalline cellulose (MCC), a recyclable natural product. The surface features of the novel Ce-BTC@MCC composite were carefully investigated through infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and N2-adsorption/desorption. The ratio of Ce-BTC to MCC in the composite was systematically optimized based on adsorption performance experiments. The developed Ce-BTC@MCC composite significantly outperformed its individual components (Ce-BTC and MCC) in removing Congo Red (CR) dye from water. This enhanced performance is due to the synergistic effect between Ce-BTC and MCC, which enhances the adsorption capacity of the designed composite. A comprehensive investigation was conducted to assess the impact of various parameters, including contact time, pH, temperature, and initial concentration, on the adsorption process. The experimental adsorption data for CR were well-described by the Langmuir isotherm model. The optimized Ce-BTC@MCC composite (20 wt% Ce-BTC content) demonstrated a remarkable maximum adsorption capacity of 926.3 mg/g for CR. The adsorption kinetics followed a pseudo-second-order model (R2 = 0.988), and both intraparticle and boundary layer diffusion influenced the rate-limiting step of the adsorption process. A plausible mechanism for the adsorption of CR onto the Ce-BTC@MCC surface was proposed. The results highlight the effectiveness, selectivity, and reusability of the eco-friendly Ce-BTC@MCC adsorbent for removing CR from different real water samples.